Constelações de vagalumes: Bruno Schulz e outros insetos fosforescentes no cosmos da palavra poética - Martins, Élida Mara Alves Dantas (2020)
As though mapping from an astronomical perspective the incidence of the spirit of art upon humanity, in an essay from 1935, named “Assim nascem as lendas”, writer and painter Bruno Schulz, the figure around which I constellate the reflections in this thesis, paints only with words the following comisc landscape: “greatness is shared sparsely, in small doses, over the world map, like sparkles of a precious metal over the acres of a rock garden”. With his senses of poet, Schulz professes his creed in the fact that the true artists have gone into extinction as soon as the nineteenth century digested its last great man, its last precious metal. According to him, after that, humanity breathed relieved, swearing not to give birth no any else. Four decades later, in 1975, elsewhere on the globe, in an article named “O vazio do poder na Itália”, Italian film-maker Pier Paolo Pasolini, with an equally pessimist tonality and with the same sense of responsibility featured by Schulz, announced a similar vanishing: the spirit of the people, the human spirit itself has disappeared from the heart of society. Alike the Polish writer, the film-maker defines this phenomenon with a poetic-literary image: the precious metals that the Polish saw disappearing assumed, in the eyes of the Italian, a different form of light, that of the fireflies. Ahead in time, in 2009, in a luminous gesture of solidarity, french philosopher and art historian Georges Didi-Huberman revisits Pasolini’s universe, follows the trail of his sparkles, and comes back to us with hope put upon the Survival of fireflies. Inspired by Didi-Huberman, I track the reticular layout of Schulz, Pasolini and other phosphorescent insects of art, like Israeli writer David Grossman, to contemplate, in the cosmos of poetic word, how a constellation of firefly-artists is formed, writers who, contrary to their own pessimistic feelings, have appropriate of a poetical force with inversely proportional power to that of the destructive forces. Based upon another of Schulz’s artistic-philosophic essays, named “Mitificação da realidade”, from 1936, and also combining his notions to the contributions of other artists composing the same constellation as him, I propose to reflect on the poetic word as an organizing force of the universe, as a founder of art, as the spirit of artistic creation itself. I understand this force as the magnetic field that connects the great artists dispersed around humanity and their works, but also as the element that orders our own universes when, in the condition of readers and researchers of literature, we expose ourselves to the radiation of the constellations of art. It is in this multiverse of creation, reception and literary criticism that I come close to Didi-Huberman saying that “the fireflies, it depends on us not seeing them disappear. Well, for this, we ourselves must assume certain freedom of movement”. Therefore, the development of this thesis was the path I found to assume such freedom. It is an outgrowth of certain desire, of certain hope that even us researchers of art share, even though we are not always allowed to assume it: a hope and desire that the fireflies resist and inhabit among us.